2015
DOI: 10.1111/ddi.12401
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Darwin's Naturalization Conundrum in the San Juan Islands using community phylogenetics and functional traits

Abstract: Aim Darwin posed a conundrum about species invasions, postulating the importance of functional distinctiveness from the receiving native community to avoid competition, and, at the same time, the importance of shared similarity to pass environmental filters and successfully establish. Using phylogenetic distances and functional traits, we assessed this conundrum in the flora of 80 mostly uninhabited islands, where over 30% of the species are invasive. We highlight the importance of publicly available datasets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 64 publications
4
53
1
1
Order By: Relevance
“…The infrequent application of such approaches (Cross et al., ; Dainese & Bragazza, ) suggests we are still a long‐way from developing robust generalisations about plant invasions. For example, comparisons of trait differences between native and alien species are still undertaken at regional scales (Bezeng, Davies, Yessoufou, Maurin, & Van der Bank, ; Kuester, Conner, Culley, & Baucom, ; Marx, Giblin, Dunwiddie, & Tank, ) even though the relevance of such analyses for understanding the vulnerability of plant communities to plant invasion is debatable. The increasing availability of plot‐scale data world‐wide (Chytry et al., ; Rutherford, Mucina, & Powrie, ; Walker et al., ) has the potential to herald considerable new insights into the role that trait differences between native and alien species may play in plant invasions and facilitate the application of methods that account for spatial scale dependence, environmental gradients and even temporal variation in species composition.…”
Section: Discussionmentioning
confidence: 99%
“…The infrequent application of such approaches (Cross et al., ; Dainese & Bragazza, ) suggests we are still a long‐way from developing robust generalisations about plant invasions. For example, comparisons of trait differences between native and alien species are still undertaken at regional scales (Bezeng, Davies, Yessoufou, Maurin, & Van der Bank, ; Kuester, Conner, Culley, & Baucom, ; Marx, Giblin, Dunwiddie, & Tank, ) even though the relevance of such analyses for understanding the vulnerability of plant communities to plant invasion is debatable. The increasing availability of plot‐scale data world‐wide (Chytry et al., ; Rutherford, Mucina, & Powrie, ; Walker et al., ) has the potential to herald considerable new insights into the role that trait differences between native and alien species may play in plant invasions and facilitate the application of methods that account for spatial scale dependence, environmental gradients and even temporal variation in species composition.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, most studies exploring the effects of phylogenetic relatedness between invasives and natives on community resistance (i.e. phylogenetic species‐based indices) have yielded mixed (Jones et al , Liu et al , Poe , Lososová et al , Marx et al ) or non‐significant results (Castro et al , Fleming et al ). Nevertheless, a recent study by Tan et al () in a manipulative experiment with bacterial assemblages found evidence that phylogenetic relatedness to invaders was a better predictor of biotic resistance than the phylogenetic diversity of the community.…”
Section: ) Which Communities Are More Resistant To Invasion?mentioning
confidence: 99%
“…Schaefer et al (2011), Park and Potter (2013, 2015a,Li et al (2015a),Marx et al (2016) Ranked difference indices The standardized mean differences in trait values between the invader and each native species in the community.…”
mentioning
confidence: 99%
“…Therefore, overall, our study shows that while patterns of phylogenetic relatedness among non-native and native species within a community can offer insight into a community's susceptibility to invasion, phylogenetic relatedness alone may be an insufficient predictive tool for understanding the rules of community assembly. Rather, future efforts integrating phylogenetic diversity with other measures, such as phenotypic traits (e.g., Gaynor, Ng, & Laport, 2018;Marx et al, 2016;Schaefer et al, 2011), and abiotic factors (e.g., Lim, Crawley, De Vere, Rich, & Savolainen, 2014;Qian & Sandel, 2017), will help elucidate whether phylogenetic relatedness together with other factors can be used to predict a community's susceptibility to the establishment of new species.…”
Section: Darwin's Naturalization Conundrum Persistsmentioning
confidence: 99%
“…Although many early studies used taxonomy-based metrics of species relatedness following Darwin (e.g., comparing generic affinities), the increased availability of sequence data and computing power has led to a rise in the number of studies testing DNC with metrics that quantify relatedness from phylogenetic relationships (Gerhold et al, 2011;Strauss, Webb, & Salamin, 2006;Tan, Pu, Ryberg, & Jiang, 2015). These studies have revealed that the process of community assembly is more complicated than previously thought, with different studies providing support for both alternatives of DNC (reviewed in Thuiller et al, 2010;Jones, Nuismer, & Gomulkiewicz, 2013;Ma et al, 2016;Marx, Giblin, Dunwiddie, & Tank, 2016). The lack of a general pattern appears to be largely due to studies differing in temporal scale (i.e., stage of invasion) (Li et al, 2015;Ma et al, 2016), spatial scale (e.g., local versus regional) (Carboni et al, 2013;Davies, Cavender-Bares, & Deacon, 2011;Ma et al, 2016;Schaefer, Hardy, Silva, Barraclough, & Savolainen, 2011) and/or phylogenetic scale (Procheş, Wilson, Richardson, & Rejmánek, 2008;Thuiller et al, 2010).…”
Section: Introductionmentioning
confidence: 99%